Socio-economic and demographic factors associated with reproductive and child health preventive care in Mozambique: a cross-sectional study - Daca, Chanvo; Sebastian, Miguel San; Arnaldo, Carlos; Schumann, Barbara (International journal for equity in health, 2020)
Background Reproductive and child health interventions are essential to improving population health in Africa. In Mozambique, although some progress on reproductive and child health has been made, knowledge of social inequalities in health and health care is lacking. Objective To investigate socio-economic and demographic inequalities in reproductive and child preventive health care as a way to monitor progress towards universal health coverage. Methods A cross-sectional study was conducted, using data collected from the 2015 Immunization, AIDS and Malaria Indicators Survey (IMASIDA) in Mozambique. The sample included 6946 women aged 15 to 49 years. Outcomes variables were the use of insecticide treated nets (ITN) for children under 5 years, full child immunization and modern contraception use, while independent variables included age, marital status, place of residence, region, education, occupation, and household wealth index. Prevalence ratios (PR) with 95% confidence intervals (95% CI) were calculated by log binomial regression to assess the relationship between the socio-economic and demographic characteristics and the three outcomes of interest. Results The percentage of mothers with at least one child under 5 years that did not use ITN was 51.01, 46.25% of women had children aged 1 to 4 years who were not fully immunized, and 74.28% of women were not using modern contraceptives. Non-educated mothers (PR = 1.33; 95% CI: 1.16–1.51) and those living in the Southern region (PR = 1.36; 95% CI: 1.17–1.59) had higher risk of not using ITN, while the poorest quintile (PR = 1.34; 95% CI: 1.04–1.71) was more likely to have children who were not fully immunized. Similarly, non-educated women (PR = 1.17; 95% CI: 1.10–1.25), non-working women (PR = 1.09; 95% CI: 1.04–1.16), and those in the poorest quintile (PR = 1.13; 95% CI: 1.04–1.24) had a higher risk of not using modern contraceptives. Conclusion Our study showed a low rate of ITN utilization, immunization coverage of children, and modern contraceptive use among women of reproductive age. Several socio-economic and demographics factors (region, education, occupation, and wealth) were associated with these preventive measures. We recommend an equity-oriented resource allocation across regions, knowledge dissemination on the importance of ITN and contraceptives use, and an expansion of immunization services to reach socio-economically disadvantaged families in order to achieve universal health coverage in Mozambique.